Formulation and Stability Evaluation of Red Dragon Fruit (Hylocereus polyrhizus) Extract Gel - Febrianti, Novi; Widyastuti, Lina; Saputri, Septiana; Irham, Lalu Muhammad (Sciences of Pharmacy, 2025)
Red dragon fruit (Hylocereus polyrhizus) is known for its strong antioxidant properties and potential anti-aging effects. To enhance its benefits and improve usability, this fruit extract was formulated into a gel preparation. This study aimed to determine the optimal proportions of Carbopol 940 and triethanolamine (TEA) to obtain a gel with desirable physical characteristics. The flesh of red dragon fruit was juiced and concentrated to produce an 8% extract. Three formulations were prepared with varying ratios of Carbopol 940 to TEA: 0.5%:0.3% (F1), 1.2%:0.7% (F2), and 2%:1.2% (F3). The gels were evaluated for physical properties, antioxidant activity, and antibacterial activity. The most promising formula was subjected to stability testing for three cycles under different temperature conditions: cold (3 °C), room temperature (27 °C), and climatic chamber (40 °C, 75% RH). Results showed that formula F2 exhibited a characteristic red color, clear appearance, distinctive oleum rosae aroma, moderately thick and homogeneous consistency, viscosity of 3112.47 ± 177.90 cps, spreading diameter of 5.20 ± 0.20 cm, adhesion time of 18.45 ± 0.89 s, and pH of 5.33 ± 0.02. No significant changes were observed after the stability testing (p > 0.05), indicating that the formulation remained stable under all temperature conditions. F2 also showed higher antioxidant activity than F1 and better antibacterial properties than F3. Its stability and bioactivity support its potential as a promising natural cosmeceutical formulation.